Prevalence of Feline Dermatophytosis in and around Mhow (Indore), MP - Gautam, Sumit; Choudhary, Nidhi S; Gangil, Rakhi; Bagherwal, Rajendra K; Agrawal, Vivek (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Dermatophytosis (ringworm) is an important feline skin disease primarily caused by the dermatophyte genera Microsporum and Trichophyton. The present research was aimed at determining the prevalence of dermatophytes in cats in and around the Mhow region (Indore, India). A total of 137 cats were brought into the Veterinary Clinical Complex of the College in Mhow, during the study period of 6-months. The preliminary examination was done by Woods lamp examination and direct microscopy, and the confirmatory diagnosis was made by fungal cultural examination. The overall prevalence of dermatophytosis in cats was found to be 21.1% (29/137). Notably, cats less than 6 months old exhibited a higher prevalence rate of 26.58% compared to adult cats, which showed a prevalence of 13.79%. The sex-wise prevalence revealed a marginal difference, with 20.31% in males and 21.91% in females. Specimens of 29 out of 43 cats exhibiting clinical signs of dermatophytosis collected using Mackenzie’s toothbrush technique confirmed dermatophytes positive on culture. In conclusion, the data strongly support the need for a comprehensive report on local epidemiology on feline dermatophytosis with a noteworthy impact observed among cats under six months of age in comparison to other age groups.